Genetic determinants of tissue factor pathway inhibitor plasma levels - Dennis, Jessica; Kassam, Irfahan; Morange, Pierre-Emmanuel; Trégouët, David-Alexandre; Gagnon, France (Thrombosis and Haemostasis, 2015)
Tissue factor pathway inhibitor (TFPI) impedes early stages of the blood coagulation response, and low TFPI plasma levels increase the risk of thrombosis. TFPI plasma levels are heritable, but specific genetic determinants are unclear. We conducted a comprehensive review of genetic risk factors for TFPI plasma levels and identified 26 studies. We included 16 studies, as well as results from two unpublished genome-wide studies, in random effects meta-analyses of four commonly reported genetic variants in TFPI and its promoter (rs5940, rs7586970/rs8176592, rs10931292, and rs10153820) and 10 studies were summarised narratively. rs5940 was associated with all measures of TFPI (free, total, and activity), and rs7586970 was associated with total TFPI. Neither rs10931292 nor rs10153820 showed evidence of association. The narrative summary included 6 genes and genetic variants (P151L mutation in TFPI, PROS1, F5, APOE, GLA, and V617F mutation in JAK2) as well as a genome-wide linkage study, and suggested future research directions. A limitation of the systematic review was the heterogeneous measurement of TFPI. Nonetheless, our review found robust evidence that rs5940 and rs7586970 moderate TFPI plasma levels and are candidate risk factors for thrombosis, and that the regulation of TFPI plasma levels involves genetic factors beyond the TFPI gene.
Keywords: Coagulation; genetic; systematic review; meta-analysis; tissue factor pathway inhibitor